Metatarsophalangeal arthrodesis of the hallux using a minimally invasive technique - Lara, Luiz Carlos Ribeiro; Torres Filho, Lúcio Carlos de Azevedo; Cervone, Gabriel Lopes de Faria; Grajales, Juan Antonio; Bordignon, Glaucia; Lancia, Lara Furtado; Santos, Diego Vitor Braga; Marijusckin , Igor; Russo , Douglas Rocha (Journal of the Foot & Ankle, 2021)
Objective: To evaluate the outcomes of the metatarsophalangeal arthrodesis (MTPA) of the hallux using a percutaneous technique. Methods: The MTPA of the hallux was performed in a total of 27 feet: 20 patients diagnosed with hallux rigidus and 7 with rheumatoid arthritis. The mean postoperative follow-up time was 30.7 months. The results were evaluated using the visual analogue scale (VAS) for pain, the American Orthopaedic Foot & Ankle Society (AOFAS) forefoot score, and regards to union rate. Results: All 27 patients were operated percutaneously and noticed relief of the pain, with a mean increase of 50.9 points in AOFAS scores and a mean decrease of 7.4 points in the VAS. The mean union time was 10 weeks. There were no cases of nonunion. Conclusion: Percutaneous first MTP arthrodesis proved effective for treating hallux rigidus and degenerative rheumatic pathologies. Level of Evidence IV; Therapeutic Studies; Cases Series.